Yet another paradigm change? Narratives and competing policy paradigms in Brazilian labour market policies. Issue 3 (14th August 2019) - Vogeler, Colette S
ABSTRACT: When policy paradigms compete for sovereignty, a well thought-out narrative story is essential to arguing why one paradigm is superior to another. Narrative stories can be applied to underline the imperative for paradigmatic policy change. Combining Hall's work on policy paradigms with Stone's conceptualisation of narrative stories, this article explores how narrative stories are applied to support or oppose competing policy paradigms and proposes that the systematic analysis of narrative stories fosters a better understanding of policy paradigms. The case of labour market policy in Brazil is used to exemplify the argument: 13 years of Workers' Party rule induced far-reaching changes in Brazilian social and labour market policy based on demand-orientation. Following the impeachment of President Rousseff, interim-President Temer initiated major labour reforms, reviving liberal narratives. This article explores how these policy changes are representative of the competition between policy paradigms, which are reflected in party-political competition, and how recent paradigm change is supported by the construction of narrative stories.